Self-supporting hybrid silica membranes with 3D large-scale ordered interconnected pore architectures. Issue 25 (21st March 2015) - Han, Chang; Li, Meng-Ya; Li, Ying-Ning; Liu, Han-Lan; Wang, Ping; Collinson, Maryanne M.; Lu, Zhe-Xue
<x xml:space="preserve">Abstract</x> Transferrable, self-supporting membranes with unique hierarchical, interconnected pore architectures over a large length scale, have been developed.